Covenant the framework of God's grand plan of redemption - Block, Daniel Isaac 1943- (Grand Rapids Baker Academic, 2021)
A leading scholar helps readers understand the big picture of the Bible through the lens of God's covenants with humanity as they play out in both the First and the New Testaments.
Intro -- Endorsements -- Title Page -- Copyright Page -- Dedication -- Contents -- Illustrations -- Preface -- Abbreviations -- Introduction -- Part 1: The Cosmic and Adamic Covenants -- 1. The Cosmic Covenant -- 2. The Adamic Covenant -- Part 2: The Israelite Covenant -- Stage 1 of the Israelite Covenant -- 3. The Origins of the Abrahamic Covenant -- 4. The Afterlife of the Abrahamic Covenant -- Stage 2 of the Israelite Covenant -- 5. The Establishment of the Israelite Covenant at Sinai -- 6. The Renewal and Completion of the Israelite Covenant at Sinai -- Stage 3 of the Israelite Covenant -- 7. Reaffirming the Covenant on the Plains of Moab -- 8. The Nature of the Covenant Rituals and Laws on the Plains of Moab -- Stage 4 of the Israelite Covenant -- 9. The New Israelite Covenant -- Part 3: The Davidic Covenant -- 10. The Historiographic Context, Nature, and Significance of the Davidic Covenant -- 11. The Afterlife of the Davidic Covenant in Israelite Prophecy -- 12. The Afterlife of the Davidic Covenant in the Psalter -- Part 4: Covenant in the New Testament -- 13. The Cosmic and Adamic Covenants in the New Testament -- 14. Stage 1 of the Israelite Covenant in the New Testament -- 15. Stages 2 and 3 of the Israelite Covenant in New Testament Narratives -- 16. Stages 2 and 3 of the Israelite Covenant in the Epistles -- 17. Stage 4 of the Israelite Covenant in the New Testament -- 18. The Davidic Covenant in the Gospel Accounts of Jesus' Early Life and Ministry -- 19. The Davidic Covenant in the Gospel Accounts of Jesus' Passion and Resurrection -- 20. The Davidic Covenant in the Remainder of the New Testament -- Conclusion -- For Further Reading -- Bibliography of Works Cited -- Author Index -- Hebrew and Greek Expressions Index -- Subject Index -- Scripture and Ancient Sources Index -- Back Cover.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books